2021
DOI: 10.20452/pamw.15893
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related risk of in-hospital death in Silesia, Poland

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…This reduction was not the result of a lack of hospital beds but rather caused by the limited degree of clinical signs and symptoms, which allowed for home management of these patients. The overall mortality in our whole study cohort (8.0%) was similar to that previously reported in the SOT population [15] and also in the local general population [16], although in a recent meta-analysis of a large SOT cohort, the overall mortality was as high as 18.6%. Of note, among ICU patients we noted extremely high mortality, similar to the recent report in comparable transplant [17] and dialysis cohorts [18].…”
Section: Discussionsupporting
confidence: 89%
“…This reduction was not the result of a lack of hospital beds but rather caused by the limited degree of clinical signs and symptoms, which allowed for home management of these patients. The overall mortality in our whole study cohort (8.0%) was similar to that previously reported in the SOT population [15] and also in the local general population [16], although in a recent meta-analysis of a large SOT cohort, the overall mortality was as high as 18.6%. Of note, among ICU patients we noted extremely high mortality, similar to the recent report in comparable transplant [17] and dialysis cohorts [18].…”
Section: Discussionsupporting
confidence: 89%
“…This observation is in line with epidemiological data on COVID-19 mortality in different age groups [ 21 , 22 , 24 ]. A study in a group of 2830 patients hospitalized with COVID-19 in one of the administrative regions in Poland (Silesia Voivodeship) showed that COVID-19 deaths were associated with male sex (OR: 1.52; 95%CI: 1.17–1.96), older age (OR: 6.11; 95%CI: 4.5–8.31), and the presence of 2 (OR: 3.05; 95%CI: 2.07–4.51) or ≥3 coexisting diseases (OR: 4.78; 95%CI: 3.52–6.49) [ 25 ]. In our study when controlled by age and sex, the presence of at least one comorbidity more than doubled the COVID 19–related risk of in-hospital death.…”
Section: Discussionmentioning
confidence: 99%
“…In our study when controlled by age and sex, the presence of at least one comorbidity more than doubled the COVID 19–related risk of in-hospital death. The differences may result from the fact that the study from Silesia Voivodeship [ 25 ] was limited to the first wave of COVID-19 pandemic (March–June 2020) and our study includes data covering the entire 2020 (two waves of COVID-19 pandemic).…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, by the end of 2020, the COVID-19-related overall mortality rate was 2.1% with an 11.5% estimated in-hospital fatality rate for COVID-19 during the first wave of the pandemic [ 9 ]. The treatment of COVID-19 with tocilizumab was initiated in April 2020, as the drug was already registered in Poland.…”
Section: Introductionmentioning
confidence: 99%